2014
DOI: 10.5367/te.2013.0277
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Small Area Demand for Grocery Retailers in Tourist Areas

Abstract: This paper uses data from a major loyalty card scheme to draw insights about the characteristics of grocery expenditure by tourists. The authors explore the volume, value and composition of storebased visitor expenditure using consumer data from the loyalty card scheme. They focus on grocery spending at selected stores in Cornwall, a popular tourist destination in South West England. The loyalty card data provide a valuable source rarely available for academic investigations. The authors are able to analyse vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 12 publications
(13 reference statements)
0
11
0
Order By: Relevance
“…Occupancy rates for commercially operated accommodation are routinely collected and reported (see White 2010) and have been used to determine seasonal patterns of accomodation utilization. No nationally representative survey of visitor spend on groceries exists in the United Kingdom (although key headline surveys such as the United Kingdom Tourism Survey contain broader spending categories); however, surveys by key trade organizations such as the British Holiday and Home Parks Association (BH & HPA 2012) provide an excellent indication of grocery spend associated with visitors and have been used, in conjunction with loyalty card analysis (reported fully in Newing et al 2014) to apply seasonal visitor grocery expenditure rates to the occupied accomodation stock.…”
Section: Date (Week Ending)mentioning
confidence: 99%
“…Occupancy rates for commercially operated accommodation are routinely collected and reported (see White 2010) and have been used to determine seasonal patterns of accomodation utilization. No nationally representative survey of visitor spend on groceries exists in the United Kingdom (although key headline surveys such as the United Kingdom Tourism Survey contain broader spending categories); however, surveys by key trade organizations such as the British Holiday and Home Parks Association (BH & HPA 2012) provide an excellent indication of grocery spend associated with visitors and have been used, in conjunction with loyalty card analysis (reported fully in Newing et al 2014) to apply seasonal visitor grocery expenditure rates to the occupied accomodation stock.…”
Section: Date (Week Ending)mentioning
confidence: 99%
“…This represents a total visitor spend on groceries in any given week of £3.57m, distributed across the county. Newing et al (2012;2014) strongly argued that this approach was misleading and suggested that it failed to account for a number of characteristics of visitor demand -most notably the spatial distribution of visitor accommodation, differences in the volume and value of visitor expenditure compared to residential expenditure, and seasonal variations in visitor demand, none of which are accurately handled in the estimations based on the simple up-scaling of residential demand.…”
Section: Approaches For Estimating Visitor Demandmentioning
confidence: 99%
“…In common with Newing et al (2012;2014) we have store trading data for four supermarkets operated by a major grocery retailer within Cornwall. We are therefore able to compare the estimated store revenue using the SIM with the actual revenue recorded in store by the company, although to preserve confidentiality we are unable to reveal the retailer or location of the stores themselves.…”
Section: Small Area Visitor Grocery Demand Estimatesmentioning
confidence: 99%
See 2 more Smart Citations